Development of a toroidal-shaped differential mobility analyzer for effective measurements of airborne particles: Experiment and modeling. Issue 4 (2nd April 2020) - Lee, Handol; Lee, Gun Ho; Ahn, Kang-Ho
Abstract: A toroidal-shaped differential mobility analyzer (DMA), called toroidal Hanyang-DMA (toroidal Hy-DMA), was developed for particle characterization. The height, width, and weight of the newly developed toroidal Hy-DMA are 8 cm, 14 cm, and 1.2 kg, respectively, indicating that it is much more compact and lighter than the TSI long-DMA; nevertheless, the classifiable particle size range is up to 400 nm. Therefore, the toroidal Hy-DMA can be useful for many applications in a limited space owing to its small size. The performance of the Hy-DMA was evaluated using tandem differential mobility analyzer (TDMA) experiments with two identical Hy-DMAs and numerical simulations using a single-particle tracking analysis in a Lagrangian framework. To simulate particle behaviors, a flow-rate-weighted particle injection method, which is more realistic, was employed, and the proposed particle tracking method can be widely applied to any non-plug flow conditions. The obtained experimental data and numerical results of central particle sizes are consistent with each other. Empirical and numerical transfer functions of the toroidal Hy-DMA were obtained and compared with those of other types of well-known DMAs. It is concluded that the toroidal Hy-DMA has an empirical transmission probability ranging from 0.5 to 0.9 and a sizing resolution ranging from 5.5 to 9.0, which indicates acceptable performance in classifying monodisperse particles within the test size range of 20 to 400 nm. Copyright © 2019 American Association for Aerosol Research